DETERMINASI TRANSFER PRICING PADA PERUSAHAAN TAMBANG DI INDONESIA - Ratnasari, Merry; Widiastuti, N.P.E; Sumilir, Sumilir (Jurnal Akunida, 2021)
This study aims to analyze the effect of tax planning, tunnelling incentive, debt covenant, and intangible asset on the decision on transfer pricing in mining companies listed on the Indonesian Stock Exchange in 2017 – 2019. This research uses quantitative research methods with secondary data from company financial and annual reports. The hypothesis testing used is panel data with random effect model. Based on the result of data analysis, it can be concluded that tax planning, debt covenant, and intangible asset has no effect on the decision on the transfer pricing. This indicates that the amount of the effective tax rate, the interest ratio, and the sale of intangible asset do not affect the company’s decision on transfer pricing. Meanwhile, tunnelling incentive has positive effect on the decision on the transfer pricing, which indicates that the amount of the tunnelling incentive activities affect the company’s decision on transfer pricing.